Evaluasi Pengendalian Intern Siklus Pengajian dan Kepegawaian pada Shoe Industry - Paddery (Jurnal Ilmiah Raflesia Akuntansi, 2019)
- In general, a company established to make a profit. In terms of getting the profits, that companies need the tools of labor which is often called the employee or employees. Within the cycle there are things that need staffing for the company to employees of the payroll system. One way that companies are often used to control the activities of these personel is to use independent power inherent in the company who is often referred to Internal Audit. The role of internal auditing within a company is very important is top staffing cycle, especially in the payroll system to employees.